BADAN USAHA MILIK DESA (BUMDes) DALAM SISTEM HUKUM EKONOMI NASIONAL - Wahid, Abdul; Rohadi, Rohadi; Sumartini, Siti; Mansur, Mansur (Yustitia, 2025)
The presence of BUMDes is expected that the village will become more independent and the community will become more prosperous. But considering that BUMDes is still a new thing in its existence, it is inevitable that in practice, several obstacles arise precisely related to the process of its formation. the existence of BUMDes, both in terms of the role and regulation of the law and in the implementing regulations, there are still deficiencies, especially its position as a form of business entity. The problem of this research is what is the position of BUMDes in the legal system of the national economy and what is the role of BUMDes in the national economic system. The research method used is normative legal research. The conclusions obtained from research on BUMDes regulations have existed since the promulgation of Law Number 22 of 1948 concerning Principles of Regional Government, then successively regulated in Law Number 1 of 1957 concerning Principles of Regional Government, Law Number 18 of 1965 regarding Principles of Regional Government, Law Number 19 of 1965 concerning Praja Villages as a Transitional Form to Accelerate the Realization of Level III Regions throughout the Territory of the Republic of Indonesia, Law Number 5 of 1974 concerning Principles of Governance in the Regions, Law Number 5 of 1979 concerning Village Government, Law Number 22 of 1999 regarding Regional Government, Law Number 32 of 2004 regarding Regional Government. Separate arrangements are made through the promulgation of Law Number 6 of 2014 concerning Village Administration. As a business entity, BUMDes plays an important role in the development and progress of the economy at the village level as the basis for the agricultural industry. The presence of BUMDes can be a tool for social engineering in the field of welfare which will function to engineer the standard of living of stagnant rural communities towards better progress in the welfare of their people.